L-shaped association of the non-high-density lipoprotein to high-density lipoprotein ratio with low bone mass disorders - Xiaoteng Chen; Wenyi Du; Hang Li; Jian Wang; Yinkang Wang; Jijun Zhao (Scientific Reports)
Abstract Osteoporosis and osteopenia, collectively referred to as Low Bone Mass Disorders (LBMD), are characterized by decreased bone density and increased fracture risk. Studies have identified a potential link between cardiovascular disease and LBMD, and the role of lipid metabolism in this has attracted widespread attention. We analyzed participant information collected from multiple NHANES cycles using weighted multivariable logistic regression, subgroup analysis, restricted cubic splines (RCS) curve analysis, and causal mediation analysis. Non-high-density lipoprotein to high-density lipoprotein ratio (NHHR) was significantly negatively associated with low bone mass disorders in a fully adjusted model. We found that NHHR exhibited an L-shaped relationship with the prevalence of LBMD, with a negative association when NHHR < 3.38 and no significant association when NHHR > 3.38. So we could manage both disorders through NHHR. Causal mediation analysis demonstrated that NHHR was a partial mediator of the effect of body mass index (BMI) on low bone mass disorders (LBMD), accounting for 2.3% of the total effect. This suggests that part of the effect in weight affecting low bone mass disorders is mediated by the NHHR. This inspires us to utilize NHHR to guide weight management.